Engagement, Satisfaction, and Belonging of International Undergraduates at U.S. Research Universities - Van Horne, Sam; Lin, Shuhui; Anson, Matthew; Jacobson, Wayne (Journal of International Students, 2018)
International students face challenges that their U.S. classmates rarely encounter, but few studies examine specific ways in which undergraduate experiences of international students compare to those of their U.S. classmates. This study examines U.S. and international student responses to an undergraduate survey administered at nine U.S. research universities in order to identify similarities and differences in ways that these two groups perceive their experiences. Findings suggest that in many ways, experiences with faculty for the two groups are more similar than different. However international students consistently report lower levels of social satisfaction and feelings of being welcome and respected on campus, suggesting that interactions among students are a significant factor in international student sense of belonging at the university.